Towards Enantioselective Rhodium-Catalysed Addition of Alkenylboron Species to Azinium Salts - Bentley, K.B. (2021)
Described is the rhodium-catalysed addition of alkenylboron species to azinium salts. Previous work has demonstrated this addition is limited to azinium salts with an ester electronwithdrawing group (EWG) at the C3 position or when quinolinium salts are used. This work plans to expand the scope of the azinium salts to include alternative EWGs, such as the nitro and cyano group, at the C3 position. It is important to note, azinium salts with an EWG at the C3 position can be attacked at three different carbon centres: C6, C4 and C2. Therefore, poor regioselectivity is expected as addition will lead to multiple products. Within the literature, selective addition at C6 is recorded with residual addition at C4 or C2, this work reports selective C2 and C6 addition. Investigations into the scope of the alkenylboron reagent and azinium salt are performed to understand their effect on regioselectivity and yield. Furthermore, the reaction conditions are optimised towards a highly yielding and regioselective addition. Finally, this work includes investigations into an enantioselective variant of this addition by evaluating a range of chiral ligands.